Sleep duration, spot urinary 6‐sulfatoxymelatonin levels and risk of breast cancer among Chinese women in Singapore. Issue 4 (28th June 2012) - Wu, Anna H.; Stanczyk, Frank Z.; Wang, Renwei; Koh, Woon‐Puay; Yuan, Jian‐Min; Yu, Mimi C.
Abstract We previously reported an inverse association between sleep duration and breast cancer risk in the prospective, population‐based Singapore Chinese Health Study (SCHS) cohort (Wu et al., Carcinogenesis 2008;29:1244–8). Sleep duration was significantly positively associated with 6‐sulfatoxymelatonin (aMT6s) levels determined in a spot urine, but aMT6s levels in breast cancer cases were lacking (Wu et al., Carcinogenesis 2008;29:1244–8). We updated the sleep duration–breast cancer association with 14 years of follow‐up of 34, 028 women in the SCHS. In a nested case–control study conducted within the SCHS, randomly timed, prediagnostic urinary aMT6s concentrations were compared between 248 incident breast cancer and 743 individually matched cohort controls. Three female controls were individually matched to each case on age at baseline interview (within 3 years), dialect group, menopausal status, date of baseline interview (within 2 years), date of urine sample collection (within 6 months) and timing of urine collection during the day (within 1 hr). Cox proportional hazards and conditional regression models with appropriate adjustment for confounders were used to examine the sleep– and aMT6s–breast cancer relationships. Breast cancer risk was not significantly associated with sleep duration; adjusted odds ratio (OR) for 9+ vs. ≤6 hr is 0.89 [95% confidence interval (95% CI) = 0.64–1.22]. Prediagnostic aMT6s levels did not differ between breast cancer cases and matched controls; adjusted OR for highest versus lowest quartiles is 1.00 (95% CI = 0.64–1.54). We conclude that sleep duration is not significantly associated with breast cancer risk reduction. Melatonin levels derived from randomly timed spot urine are unrelated to breast cancer. Randomly timed, spot urine‐derived melatonin levels are noninformative as surrogates of nocturnal melatonin production.